Gambaran Perilaku Need for Achievement pada Relawan di Organisasi Nirlaba - Almaida Marthasari; Budi Sarasati; Yomima Viena Yuliana (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
This study aims to provide an overview of the need for achievement behavior among fully voluntary participant in nonprofit organization. The volunteers of a nonprofit organization have a crucial role in the organization, but their participation often fluctuates significantly. Researchers suspect that this is closely related to the individual's psychological health condition, specifically the level of need for achievement (n-Ach). This research uses a descriptive quantitative method with a modified McClelland need for achievement scale instrument, to adapt to the context of nonprofit organizations. The sampling technique used nonprobability sampling and convenience sampling of 128 active volunteers from various backgrounds. The results showed that n-Ach in volunteers could be described in the high, medium, and low categories, then through the Mann-Whitney U-Test there was no significant difference based on gender and duration of volunteer involvement. This research is expected to contribute to understanding volunteer motivation, becoming a reference and implications for policy development and volunteer management in nonprofit organizations.